Inovasi Pembelajaran Hadis: Menggali Signifikansi Melalui Metode Saintifik dan Multidisipliner - Nofiyanti, Fitria; Miftah, Muhammad (el Buhuth: Borneo Journal of Islamic Studies, 2025)
This research aims to explore the implementation of innovation in the hadith learning process through scientific and multidisciplinary approaches at Madrasah Ibtidaiyah (MI) Manafiul Ulum Kudus. This study uses a qualitative method with data collection techniques: interviews, observation, and documentation. Interviews were conducted with the head of the madrasah, teachers, and students to explore their learning experiences. The research findings identify that the application of scientific methods and multidisciplinary approaches has successfully deepened students' understanding of Islamic teachings and their relevance to daily life. Students not only memorize the hadith texts but also understand the meaning and significance of these teachings in social and cultural contexts. This research also found that innovation in learning can build students' critical and analytical thinking skills and strengthen their character through reflection on moral values. Further research is recommended to explore the effectiveness of innovative methods in various other Islamic educational institutions, as well as identify potential challenges in their implementation. Thus, the hope from this research is that it can significantly contribute to the advancement of Islamic education, especially hadith, which is more relevant and contextual in Indonesia